Algebra

posted by Joy

Find ​(f◦​g)(x) and ​(g◦​f)(x).
f(x)=4x(squared)+3​; ​g(x)=4x−2(f◦​g)(x)=______(Simplify your​ answer.)
I keep getting lost on these f(x) and g(x)problems

  1. Steve

    ​(f◦​g) = f(g) = 4g^2+3 = 4(4x-2)^2+3
    ​(g◦f) = g(f) = 4f-2 = 4(4x^2+3)-2
    now just simplify

    sometimes it helps not to include all those (x)'s
    ​(f◦​g)(x) = f(g(x)) = f(4x-2) = 4(4x-2)^2+3
    you can replace g first or evaluate f(g) and then plug in g

Respond to this Question

First Name

Your Answer

Similar Questions

  1. math

    How do i find the area of a triangle? For example: A squared + b squared= c squared 8.5 squared + 6.4 squared= c squared 72.25 + 40.96= c squared 113.21=c squared 10.6400188=c even tho i thought this was the answer it is not because
  2. Math (Algebra)

    The width of a rectangle is fixed at 7cm. Determine (in terms of an inequality) those lenghts for which the area will be less than 161cm squared. The length must be less than ?
  3. algebra

    Please help me! Sorry there are 4 questions I need to check my attempts with to see if I am on track. Thanks!! 1. 5-3[2(3x-4)+3] 2. Evaluate when x = -3 and y = 2 3x squared - 4y squared _______________________ 4x - 7y 3. -3/4y = -24 …
  4. algebra

    Please help me! Sorry there are 4 questions I need to check my attempts with to see if I am on track. Thanks!! 1. 5-3[2(3x-4)+3] 2. Evaluate when x = -3 and y = 2 3x squared - 4y squared _______________________ 4x - 7y 3. -3/4y = -24 …
  5. Math

    Using the example: (a+b)(a+b)= a squared -b squared, we are asked to multiply and simplify (b+3d)(b-3d). Hint: Do not use distributive property. Shouldn't the answer be b squared - 9d squared?
  6. algebra 2 multiple choice HELP

    find f(a), if f(t) = 2t2(squared)-t-2 A. 2(a+t)2(squared)-2t+1-2 B. 2(t+a)2(squared)-2(t+a)-2 C. 2a2(squared)-a-2 D. 4a2(squared)-2a-2 I put (squared) because the two in front of it means it's being squared... please help. thanks!
  7. Math

    I was wondering if I solved these problems right?
  8. Math

    Find the shortcut. Solve these problems. Then find and explain a shortcut method for finding the answer. 52(Squared) - 42 (squared) = 82 (Squared) - 72 (Squared) = 122 (Squared) - 112 (Squared) = 312 (Squared) - 302 (Squared) = 892 …
  9. algebra

    how do you simplify 3j cubed - 51j squared + 210j?
  10. algebra

    in equation x - 1/x ________ x + 1/x My answer key said the answer was x squared -1 _____________ squared + 1 I'm wandering why it wouldn't simply be x-1 ______ x+1

More Similar Questions